Mengembalikan Makna Bernapas - Raymond R. Tjandrawinata (PT Dexa Medica, 2025)
The management of lower respiratory tract diseases, such as bronchitis, chronic obstructive pulmonary disease (COPD), and bronchiectasis, poses a significant challenge, particularly in countries with high levels of air pollution, smoking habits, and high prevalence of infections. Cough, as one of the primary symptoms, serves as a protective mechanism of the body to maintain airway hygiene as well as unobstructed breathing. Therefore, cough should be managed appropriately to ensure efficient mucus expectoration, one way being through the use of mucolytic agents such as bromhexine. Themodern approaches to respiratory infection management emphasize the combination of pharmacological interventions and physiological support. Pharmacological therapy focuses on restoring respiratory function using rational treatment, including control of inflammation, managing mucus drainage, and the rational use of antibiotics. Physiological interventions such as pulmonary rehabilitation and smoking cessation have a substantial long-term impact on improving patients’ quality of life.